Alfonso Reyes's "Mallarmé cult": modern poetry and the language of the polis (Revista de Crítica Literaria Latinoamericana, 2013)
This article explores Alfonso Reyes' reading of Stéphane Mallarmé, the appropriations it makes and the tensions it causes. The article examines the different phases of Reyes' reading, since the idealism of Cuestiones estéticas (1905) until the essays published in the 1950s, right before his death. Particularly, the article analyzes Reyes' reading of Mallarmé's different styles (as curator, critic, and bibliographer) and the way in which Reyes advances current debates about the relationship between Mallarmé's poetry and the Polis, as in Quentin Meillassoux's and Jacques Rancière's contemporary essays.
Keywords: Alfonso Reyes; Stéphane Mallarmé; modern poetry